Serious games evaluation methodology - Videnovik, Maja; Madevska Bogdanova, Ana; Trajkovikj, Vladimir (IATED, 2018)
Using games is a new and a powerful way of learning in the classrooms, where students are active participants in the learning process. Educational games empower students’ knowledge and skills, as well as educational value of the teaching process. There are plenty of serious games that can be used in education, but most of them simply do not hold interest among students. Thus, the students do not really accept them as games, which creates opposite effect than expected. There are other factors that influence the successful game's integration in the classroom - teachers’ digital competences, technical (pre)requirements for the game, educational value of the game. This paper presents a methodological tool based on an evaluation framework for integration of digital games into education (MEDGE). The evaluation framework uses different data gathering techniques such as: surveys, exams, observation, reflection, in order to obtain data. This methodological tool is simplified version of an evaluation framework, developed to act as a subjective, but efficient tool for teachers in order to make initial evaluation of the potential introduction of certain educational game in the classroom. The tool establishes step by step methodology for evaluation of educational games. It starts with determining the technical requirements of a game, accordance to students' age and teachers' digital competences needed to play it in the classroom. If these conditions are met, the game evaluation continues by determining game's ease of use, its educational value, students' quality of experience, game’s alignment with educational goals and teacher subjective preferences toward using the game in the classroom. The proposed methodology was tested by more than 62 teachers from Croatia, Macedonia, Norway, Estonia, Germany and Poland. The teachers were asked to evaluate at least two educational games using this methodological tool. One of those games was Kahoot, a popular game within the teachers’ community. Kahoot is a quiz based game that can be used for initial, formative and summative assessment of students’ knowledge using individual or collaborative team work mode. The other game was selected by teachers based on their needs and experiences. Using a survey with five-point Likert scale, information concerning teachers’ attitudes towards usefulness of the methodology, its complexity, applicability in the classroom, and usefulness for evaluation of a game were obtained. The participants had the opportunity to give comments and express their opinion concerning the proposed methodological tool. The paper is consisted of detailed description of the developed methodological approach, together with the use cases and results of the survey on usage of the methodological evaluation tool.
Keywords: serious games, games evaluation framework, students' QoE, evaluation methodology